PENINGKATAN KETERAMPILAN MENULIS SURAT PRIBADI DENGAN MEDIA AUDIO VISUAL (VIDEO) MATA PELAJARAN BAHASA INDONESIA KELAS IV MI HASYIM ASY’ARI JAMBANGAN CANDI SIDOARJO - Aida, Ilmi Nur (Journal Of Islamic Elementary School (JIES), 2018)
This research is motivated by the difficulty of fourth grade students to write personal letters. This is evidenced by the results of writing personal letters of almost 75% of the value under the KKM while the remaining only 25% is completed in Indonesian subjects. Therefore, this study aims to determine the application of Audio Visual (Video) media in order to improve the skills of writing personal letters on Indonesian language subjects in fourth grade MI Hasyim Asy’ari Jambangan Temple Sidoarjo. As well as to find out the improvement of skills in writing personal letters with Audio Visual media (Video) on Indonesian language subjects in fourth grade MI Hasyim Asy’ari Jambangan Temple Sidoarjo. The method used in this study is Classroom Action Research with the model of Kurt Lewin. Consisting of pre cycle, cycle I and cycle II. In the first and second cycles consisted of four stages, namely planning, action, observation and reflection. The subject of this study was fourth grade students of MI Hasyim Asy’ari Jambangan Sidoarjo Temple which consisted of 40 students. The results of the study are as follows: 1) The application of Audio Visual (Video) media runs well in cycle II. This can be seen in the results of teacher observations in the first cycle increased from 82.95 (good) to 95.23 (satisfying) in the second cycle. Similarly, student activities also increased from 77, 27 (sufficient) in the first cycle to 92.85 (satisfying) in the second cycle. This is all because the teacher is more able to pay attention to all of his students, not discriminating. So that all students get the same teaching in cycle II. 2) The increase in the skills of writing personal letters after the application of Audio Visual (Video) media can be seen from the results of the completeness of students’ writing skills increasing high. This can be seen from the average value in the pre cycle is 65.62 (less), at the stage of the first cycle is 67.4 (less) and in the second cycle becomes 89 (good).